Chemical characterisation and allelopathic potential of essential oils from leaves and rhizomes of white ginger (Revista Ciência Agronômica, 2015)
Essential oils have the potential to be used as bioherbicides, and possess the advantage of their biodegradability, highstructural diversity and reduced natural resistance to weeds. The essential oils of the leaves and rhizomes of Hedychium coronarium,an exotic invasive plant adapted to different regions of Brazil, were extracted by hydrodistillation and characterised chemically byGas-Liquid Chromatography and Gas-Liquid Chromatography/Mass Spectrometry. Allelopathic activity was determined usingmethodologies that evaluate the effects of volatility and direct contact on seed germination and seedling vigour in the lettuce. The majorconstituents of the essential oil from the leaves were ȕ-pinene (46.9%), Į-pinene (19.2%) and ȕ-caryophyllene (13.2%) and from therhizomes, ȕ-pinene (41.5%), 1.8-cineole (23.6%) and Į-pinene (13.1%). When analysing the volatile effects of the essential oils, it wasseen that their concentration did not affect seedling first germination count or total germination. The essential oil fromthe rhizomes was more effective than the essential oil from the leaves in reducing seedling response for SGI, dry weight,and length of the roots and shoots. When evaluating the effect of direct contact with the essential oils, it was seen thatboth oils reduced the response of all the variables under evaluation, and that in addition, the oil from the rhizomescaused greater reductions than that from the leaves, again for all variables. These results can be attributed to the higherlevels of monoterpenes present in the essential oil from the rhizomes, mainly the presence of 1.8-cineole.